The challenge of hyper-sexual femininity and binge drinking: A feminist psychoanalytic response - Stepney, M (Palgrave Macmillan, 2015)
In this article I examine the issue of binge drinking and the presentation of hyper-sexual femininity. Such displays present a challenge for feminism: on the one hand ‘new’ femininities have been articulated as a form of female agency and sexual empowerment, yet on the other hand it has been suggested that hyper-sexual femininity does not challenge gender hierarchies enough or in the right way and is a provocation to feminism. By taking a psychoanalytic approach (specifically Jessica Benjamin’s work) we gain explanatory strength in understanding hyper-sexual femininity through the concept of ‘splitting’. Polarities in behaviour and dress are symbolic of a deeper need for recognition in young women and are a perfectly legitimate solution to a number of contradictions, particularly in the British context. Feminist thought can therefore benefit from an engagement with psychoanalytic thought that understands why change does not happen and why normative sex roles hold considerable power.